The Genesis of a Manifold with Boundary: A Model of the Archytas Paradox - Jon Pérez Laraudogoitia (Filozoficzne Aspekty Genezy, 2024)
A geometrical model of cosmos is proposed whereby Archytas’ argument against the existence of an “edge of the heaven” does not work. The model, based on the solution to a previous paradox concerning non-rectifiable lines, demonstrates the possibility of a finite and bounded Euclidean space and reveals the purely geometrical origin of certain forces present therein.